Description of Characteristics of Participants in Class 3 in 1 Operators Yunior Custom Made Women in Balai Diklat Industries, Padang - Indah Gita Agustian; Alim Harun Pamungkas (Universitas Negeri Padang, 2020)
This research is motivated by the success of training participants in participating in training activities in the Padang Industrial Training Center. The researcher suspect that the high success achieved by the training participants is influenced by the good characteristics of the training participants in which the training participants’ interest and enthusiasm are said to be good. This can be seen from the characteristics of the participants in attending the training which consist of: cooperative type, passive type, and vandalizing type. This study aims to illustrate how the characteristics of the training participants as a benchmark for the education and training committee so that the training can be implemented well in the Padang Industrial Training Center. This type of research is quantitative descriptive research. The population in this study were participants of the 3 in 1 junior custome made female operator which amounts to 70 people. The sampling technique used was simple random sampling, in which the population in this study was 50% of the population of 35 people. Data collection techniques using a questionnaire in the form of a Likert Scale. While the data analysis technique uses the percentage formula. From the results of the study it was found that: (1) the cooperative type characteristics of the training participants were categorized as good, (2) the passive type characteristics of the training participants were categorized as less (3) the characteristics of the troubled type of the training participants were categorized as less. Based on the results of the study it is recommended that training participants can have better characters so that the training can run smoothly, and can have high motivation and good interest in participating in the training.Keywords: Characteristics, Participants, Training, Custome Made